2020
DOI: 10.1111/and.13672
|View full text |Cite
|
Sign up to set email alerts
|

The physiology of male reproduction: Impact of drugs and their abuse on male fertility

Abstract: Infertility is the failure of a couple to achieve conception after 12 months of adequate unprotected sexual intercourse (Wiwanitkit, 2008). It is a major health challenge with social implications among couples, particularly in the tropics (Yeşilli et al., 2005). Although Mascarenhas, Cheung, Mathers, and Stevens (2012) suggested a dearth of data on the global prevalence of infertility, Boivin, Bunting, Collins, and Nygren (2007) documented that about 72.4 million couples experience fertility problems globally.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 269 publications
(355 reference statements)
0
32
0
Order By: Relevance
“…The need to increase libido, potency and sexual pleasure might be the reason young adults engage in illicit drug use. Recreational drug use has been implicated in the aetiopathogenesis of infertility including male fertility (Ajayi & Akhigbe, 2020a, 2020b, 2020cKatz & Mazer, 2009;Turek et al, 1995). This study assessed the effect of Rohypnol, a commonly abused drug, on sexual behaviour in animal model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The need to increase libido, potency and sexual pleasure might be the reason young adults engage in illicit drug use. Recreational drug use has been implicated in the aetiopathogenesis of infertility including male fertility (Ajayi & Akhigbe, 2020a, 2020b, 2020cKatz & Mazer, 2009;Turek et al, 1995). This study assessed the effect of Rohypnol, a commonly abused drug, on sexual behaviour in animal model.…”
Section: Discussionmentioning
confidence: 99%
“…Co-ordination of the hypothalamic-pituitary-testicular axis is important for sexual activity. It influences male reproductive function as well as production of testosterone and prolactin (Ajayi & Akhigbe, 2020b;Corradi et al, 2016). Hypothalamic secretion of gonadotropin-releasing hormones (GnRH) stimulates the biosynthesis of luteinising hormone (LH) and follicle-stimulating hormone (FSH) which are vital in maintaining optimal production of testosterone (Ajayi & Akhigbe, 2020b;Corradi et al, 2016).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Human and animal studies have implicated several drugs, including drugs that are commonly abused such as codeine, in male infertility [ 27 ]. Although, our previous studies reported that codeine impaired male fertility, testicular and sperm integrity with their functions [ 4 , 5 , 7 ] via oxidative damage and caspase 3-mediated apoptosis, there are still some shortcomings.…”
Section: Introductionmentioning
confidence: 99%
“…GABA receptors have been identified not only in the central nervous system, but also in many non‐neuronal peripheral tissues (Ajayi & Akhigbe, 2020; Kaewman et al., 2018; Taniyama et al., 1983; Teng et al., 2013). Their presence was confirmed in, among others, structures of the male and female reproductive system, including testes, epididymis, vas deferens, ovaries and oviducts (Kanbara et al., 2005).…”
Section: Introductionmentioning
confidence: 99%